Painless Cardiac Ischemia in Women with Rheumatoid Arthritis - Toirov Doston Rustamovich; Khusainova Munira Alisherovna; Uzokov Jurabek Baxtiyorovich; Mukhiddinov Madumar Abdurakhmonovich (Zien Journals, 2022)
Rheumatoid arthritis (RA) is an autoimmune rheumatic disease of unknown etiology characterized by chronic erosive arthritis and systemic inflammatory damage to internal organs. In Uzbekistan, RA affects about 1.5% of the entire adult population. RA most often affects people aged 30-50 years. Women get sick 5 times more often than men. The main cause of mortality in RA are cardiovascular catastrophes (myocardial infarction (MI), cerebral stroke (СS) den cardiac death (SCD). Let's start the discussion with the already established facts and try to clarify the mechanisms of the changes in the heart. So,rheumatoid arthritis (RA) is an autoimmune joint disease that affects 0.5–1.0% of the world's population. In RA, almost all joints are involved in the pathological process, almost always the joints of the hand, foot and knee joints, with the development of stiffness, pain and, eventually,destruction of bone and cartilage. It is known that RA is a systemic process in which not only joints are affected, but also various internal organs. However, until recently, it was believed that heart damage in RA was clinically insignificant. In recent years, it has been found that patients with RA, life expectancy decreases by 7-10 years, and the risk of coronary disease or myocardial infarction is comparable to that of diabetes mellitus. In general, patients with RA, the risk of development is approximately 50% higher cardiovascular events and cardiovascular death. At the same time, it should be taken into account that the magnitude of these risks may vary in different studies, which is associated with the characteristics of the examined cohorts of patients, with the peculiarities of treatment in different countries, with the effectiveness of achieving or not achieving the goal of treatment, depends on the time of observation and the specifics of the therapy performed. Thus, there are indications that the combined relative risk is 1.68 and 1.87 for myocardial infarction and congestive heart failure, respectively, and another study found that patients with RA had an increased risk of myocardial infarction (MI) with a odds ratio (OR) of 2.50 (95% CI; 0.77–8.14)
Keywords: rheumatoid arthritis; coronary heart disease; characteristics; increased